2022
DOI: 10.5603/arm.a2022.0017
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities Influence the Predictive Power of Hematological Markers for Mortality in Hospitalized COVID-19 Patients

Abstract: Introduction: Coronavirus disease 2019 (COVID-19) pandemic has caused unprecedented mortality and has stretched the health infrastructure thin worldwide, especially in low- and middle-income countries. There is a need to evaluate easily available biomarkers for their clinical relevance for poor outcomes in severe cases of COVID-19. It is also known that comorbidities affect these biomarkers with or without COVID-19. We aimed to unearth the influence of comorbidities on feasible hematological predictive markers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…These findings indicate that the number of comorbidities and age significantly influence the serum levels of biomarkers in patients with COVID-19. This is consistent with the findings of Parthasarathy et al who showed a higher impairment of laboratory determinants in the group with more number of comorbidities [ 16 ]. They also reported a similar positive correlation between the laboratory parameters and the CCI score.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings indicate that the number of comorbidities and age significantly influence the serum levels of biomarkers in patients with COVID-19. This is consistent with the findings of Parthasarathy et al who showed a higher impairment of laboratory determinants in the group with more number of comorbidities [ 16 ]. They also reported a similar positive correlation between the laboratory parameters and the CCI score.…”
Section: Discussionsupporting
confidence: 93%
“…The parameters taken into account in the CoLACD score combine lymphocyte percentage, age, CCI, and the presence of dyspnea. A study conducted in Mysore, India explored the effect of the presence of multiple comorbidities on laboratory cut-offs of biomarkers [ 16 ]. For this, the study categorized patients according to CCI and compared both the biomarker values as well as the cut-offs between the different categories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be noted, the association between antibody seropositivity and CD4+, IFN-γ or IL-6 was modulated by patients’ characteristics. Such modulating impact have been previously reported for immune response immune in India [ 56 ], and haematological biomarkers of COVID-19 in Cameroon and India [ 57 , 58 ]. This is not surprising as these characteristics are well known to be predictors of SARS-CoV-2 infection, severity, or deaths [ 59 – 61 ].…”
Section: Discussionsupporting
confidence: 57%
“…Biomarkers are biological markers that can be measured accurately and reliably reproduced. It has been used extensively for various disease conditions [ 15 , 16 ]. The most commonly used biomarkers in CAP are C-reactive protein (CRP) and procalcitonin (PCT).…”
Section: Introductionmentioning
confidence: 99%